DETERMINATION OF MERCURY’S BIOACCUMULATION FACTOR IN MILK FISH (Chanos chanos) OF SEMARANG MUNICIPALITY FISHPONDS USING NEUTRON ACTIVATION ANALYSIS - Slamet Budi Prayitno (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Determination of bioaccumulation factor of mercury (200Hg) in chanos chanos of Semarang municipality fishponds has been carried out by applying the neutron activation analysis (NAA) and gamma spectrometry analysis. The gamma spectrometry technique was employed to analyze the gamma radiation exposure from activated samples. The heavy metal 200 Hg can be identified in water and milk fish (Chanos chanos), along with natural radionuclides 40K in water. The concentration of Mercury in the water at the 3 villages was 0.950 10-6 ppm, 284 10-6, and 350 10-6 ppm respectively. Whilst mercury concentration in the milk fish was 186 10-3, 068 10-3, and 098 10-3 ppm for Mangunharjo, Mangkang, dan Karanganyar respectively. Bioaccumulation factor can be estimated from the ratio of these heavy metal element in the sample and the water. Result shows that the bioaccumulation factor for mercury at 3 villages (Mangunharjo, Mangkang dan Karanganyar) is 195.942, 238.961, 279.614 respectively.